2002
DOI: 10.1152/ajprenal.00160.2002
|View full text |Cite
|
Sign up to set email alerts
|

K depletion increases protein tyrosine kinase-mediated phosphorylation of ROMK

Abstract: We purified His-tagged ROMK1 and carried out in vitro phosphorylation assays with (32)P-radiolabeled ATP to determine whether ROMK1 protein is a substrate for PTK. Addition of active c-Src and [(32)P]ATP to the purified ROMK1 protein resulted in the phosphorylation of the ROMK1 protein. However, c-Src did not phosphorylate R1Y337A in which tyrosine residue 337 was mutated to alanine. Furthermore, phosphopeptide mapping identified two phosphopeptides from the trypsin-digested ROMK1 protein. In contrast, no phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 30 publications
(43 reference statements)
5
56
0
1
Order By: Relevance
“…However, the additional mutation of WNK4 Ser 1196 to alanine restored WNK4's inhibitory effect on ROMK channels and decreased K currents to 850 ± 30 pA (n = 6). The results are consistent with the notion that c-Src acts at least in part by reducing phosphorylation at WNK4 Ser1196 (14), and that this effect is lost in the WNK4 Y1092/1094F mutant. This notion is confirmed by direct measurement of phosphorylation at this site with an antibody specific for phosphorylation at WNK4 S1196 ( Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…However, the additional mutation of WNK4 Ser 1196 to alanine restored WNK4's inhibitory effect on ROMK channels and decreased K currents to 850 ± 30 pA (n = 6). The results are consistent with the notion that c-Src acts at least in part by reducing phosphorylation at WNK4 Ser1196 (14), and that this effect is lost in the WNK4 Y1092/1094F mutant. This notion is confirmed by direct measurement of phosphorylation at this site with an antibody specific for phosphorylation at WNK4 S1196 ( Fig.…”
supporting
confidence: 90%
“…A large body of evidence has demonstrated that SFK plays an important role in inhibiting ROMK channels in the CCD (24)(25)(26)(27)(28)(29). We have previously demonstrated that SFK phosphorylates the ROMK1 channel at Tyr 337 (14) thereby facilitating internalization of ROMK channels (24). A low K intake has been shown to increase tyrosine phosphorylation of ROMK channels (11), leading to inhibition of ROMK channels and decreasing K secretion in the CCD.…”
Section: Ptp-1d Interacts With Wnk4 Via Tyr 1143 To Reduce the Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…Down-regulation of ROMK channel density in states of potassium deprivation is thought to involve Src-dependent channel endocytosis (42,43), whereas phosphorylation of one of the three PKA phosphorylation sites in ROMK (12), serine 44, has been implicated in physiological augmentation of active ROMK channel density (15). In the present study, we elucidate the molecular mechanism and identify a pathway for the hormonal regulation of the channel by vasopressin and aldosterone.…”
Section: Discussionmentioning
confidence: 83%
“…We have demonstrated previously that low K intake stimulates the production of superoxide anions and its related products, which in turn increase PTK expression and activity (4,5). Increased PTK activity stimulates tyrosine phosphorylation of ROMK channels and subsequently enhances the internalization of the ROMK channels (6,7). Furthermore, we have shown that low K intake stimulates ERK and p38 MAPK, which inhibits ROMK channels by a PTKindependent pathway.…”
mentioning
confidence: 72%